Preparation and characterization of styrene-methyl methacrylate In deproteinized natural rubber latex (SMMA-DPNR) - Che Man, Siti Hajjar (European Polymer Federation, 2007)
The graft polymerization of Styrene and Methyl methacrylate (MMA) onto deproteinized natural rubber latex (DPNR) was carried out using ammonium peroxy disulfate ( N2H8O8S2) as an initiator. The suitable reaction conditions based on the higher monomer conversion was determined. The degree of grafting and the copolymers composition of the resultant SMMA-DPNR were obtained using H-1 NMR Spectroscopy. As expected, composition of styrene in DPNR was higher than that of MMA due to the higher reactivity ratio of styrene monomer as compared to MMA monomer and the structure of the NR backbone. The mechanism of seeded emulsion polymerization leading to graft copolymer of styrene and MMA onto NR was studied and elucidated.